Tolerance of sour passion fruit cultivars to salt stress in a semi-arid region - Geovani S. de Lima; Weslley B. B. de Souza; Francisco J. da S. Paiva; Lauriane A. dos A. Soares; Rafaela A. F. Torres; Smyth T. de A. Silva; Hans R. Gheyi; Kilson P. Lopes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Given the quantitative scarcity of low-salinity water resources in the Brazilian semi-arid region, it is necessary to use water with a high concentration of salts. Thus, identifying salt-stress tolerant cultivars of crops is an alternative for expanding irrigated agriculture. The objective of this study was to evaluate the tolerance of passion fruit cultivars as a function of irrigation water electrical conductivity. The experimental design was randomized blocks, in a 5 × 3 factorial scheme, whose treatments consisted of the combination of five values of electrical conductivity of irrigation water - ECw (0.3, 1.1, 1.9, 2.7, and 3.5 dS m-1) and three sour passion fruit cultivars (BRS GA1, BRS SC1, and SCS437, with three replicates. Electrical conductivity of water from 0.3 dS m-1 reduces the relative water content, gas exchange, and the number of fruits and increased electrolyte leakage in the leaf blade of passion fruit plants, at 153 days after transplantation. The passion fruit cultivars BRS GA1, BRS SC1, and SCS437 were classified as sensitive, with threshold electrical conductivity of water of 0.3, 1.0, and 0.3 dS m-1, respectively.